Extraction and isolation of volatile oil from Pogostemon cablin (Blanco) Benth. (Fam. Labiatae) - Arban, Maria Carolina L.; Cruz, Ileana R.; Concepcion. Adoracion B. (Manila College of Pharmacy, University of the Philippines, 1989)
Volatile oils are obtained mostly from the leaves of Pogostemon cablin, a plant belonging to the family Labiatae. Patchouly oil is obtained by solvent extraction and isolated by column chromatography. The oil were concentrated and 0.43% yield were obtained. The oil color is brown with aromatic patchouly like odor, and congeals at low temperature. Presence of major constituent were determined by IR analysis.
​Thesis (Bachelor of Science in Pharmacy)--University of the Philippines, October 1989.
Keywords: Essences and essential oils; Lamiaceae; Kablin